Production of Monoclonal Antibodies against Outer Membrane Proteins of Burkholderia pseudomallei, Strain C-141 - S. S. Vetchinin; P. C. Kopylov; N. V. Kiseleva; A. M. Baranov; E. V. Baranova; E. V. Galkina; A. I. Borzilov; I. Y. Kalachev (Проблемы особо опасных инфекций, 2008)
Monoclonal antibodies (MAb) were produced against two B. pseudomallei high-purified membrane proteins with Mr 29 kDa (p29) and 45 kDa (p45). Monoclonal antibodies from culture supernatant fluids of 4F2 and 1G11 clones showed specific interaction with protein moiety of p29 both Burkholderia pseudomallei and Burkholderia mallei in ELISA and Western blotting. However, MAb of 3G4 clone were bound to the LPS-protein structures of these microbial cells. Analysis of interaction of Mabs from 4F2 and 1G11 clones with antigens of different lysates of pathogenic cells confirmed high specificity of these antibodies to p29 membrane protein of B. pseudomallei and B. mallei.